Compliance with the 2009 Royal College of Obstetricians and Gynaecologists guidelines for venous thromboembolic disease prophylaxis in pregnancy and postpartum period in Uruguay. Issue 3 (April 2018) - Grille, Sofía; Vitureira, Gerardo; Morán, Rosario; Retamosa, Lucía; Alonso, Valeria; Gómez, Luis M.; Quartara, Federico; Feldman, Florencia; López, Valentina; Turcatti, Paola; Castro, Viviana; Sosa, Leonardo; et al.
Abstract : N/A: Venous thromboembolism remains as one of the leading causes of maternal death. Prevention of venous thromboembolism in the obstetric population is challenging as recommendations for prophylaxis have low grade of evidence. Risk factors and prophylaxis guidelines have been highlighted by Royal College of Obstetricians and Gynaecologists. In 2014, we developed a written alert following this guidelines to guide thromboprophylaxis. The aim of this study is to assess recommendations compliance. This study was conducted at University-Hospital in Uruguay from January 2014 to December 2016. A total of 1035 women were enrolled and stratified in high, intermediate or low risk based on Royal College of Obstetricians and Gynaecologists guidelines. Thromboprophylaxis was recommended for women at intermediate and high risk. Women were followed up to assess symptomatic thromboembolism or haemorrhagic complications. A total of 309 were pregnant and 731 puerperal. Median age was 24 (19–29) years old. Of them, 3.0% ( n  = 31) were at high risk and 35.4% ( n  = 366) at intermediate risk. All high-risk women received prophylaxis with low-molecular-weight heparin. Of the 366 intermediate-risk women, 52.7% received prophylaxis. Venous thromboembolism was developed in only one woman of the intermediate group, who had received prophylaxis. Bleeding complications were not observed. Awareness of the thrombotic risk, as conferred by an easy and suitable risk assessment, has the potential to improve venous thromboembolism prophylaxis in pregnant and puerperal women. We have a good guidelines compliance with the written alert in the high-risk women group. However, we have to improve low-molecular-weight heparin indication in intermediate-risk group, especially in postcaesarean women.